2007
DOI: 10.1017/s0007114507749267
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulin resistance after diet with a whole-grain based dietary product: results of a randomized, controlled cross-over study in obese subjects with elevated fasting blood glucose

Abstract: Subjects with obesity and elevated fasting blood glucose are at high risk of developing type 2 diabetes which may be reduced by a dietary intervention leading to an improvement of insulin resistance. We investigated the potential of a whole-grain based dietary product (WG) with reduced starch content derived from double-fermented wheat during a hypo-energetic diet to positively influence body weight, fasting blood glucose, insulin resistance and lipids in comparison to a nutrient-dense meal replacement product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 37 publications
(50 reference statements)
2
58
0
3
Order By: Relevance
“…Different types of fibers have been reported to help control body weight, glucose and lipid metabolism, insulin sensitivity, and the regulation of many inflammatory markers 15) in both adolescents and adults [11][12][13][14] . In the present study, the mean values of fiber intake per day in male and female adolescents (9.1 and 8.5 g/day, respectively) were much lower than the recommended values for male and female Japanese adults (more than 19 and 17 g/day, respectively) 25) ; however, multivariate regression analysis revealed that fiber intake per 1,000 Kcal was the only predictor of low FPG in both genders and was the greatest predictor of low levels of ln (insulin) and ln (HOMA-IR) in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of fibers have been reported to help control body weight, glucose and lipid metabolism, insulin sensitivity, and the regulation of many inflammatory markers 15) in both adolescents and adults [11][12][13][14] . In the present study, the mean values of fiber intake per day in male and female adolescents (9.1 and 8.5 g/day, respectively) were much lower than the recommended values for male and female Japanese adults (more than 19 and 17 g/day, respectively) 25) ; however, multivariate regression analysis revealed that fiber intake per 1,000 Kcal was the only predictor of low FPG in both genders and was the greatest predictor of low levels of ln (insulin) and ln (HOMA-IR) in females.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a cluster of cardiovascular (CV) risk factors, including abdominal obesity, impaired glucose tolerance, hypertension, and dyslipidemia, which have collectively been termed metabolic syndrome in both children and adults 3,4) . It is well known that the development of CV risk factors, including obesity, is associated with adverse behavioral patterns, such as decreased physical activity [5][6][7][8] , increased sedentary lifestyle, in particular television (TV) watching [8][9][10][11] , and unhealthy dietary habits 5,[11][12][13][14][15][16] . Parental obesity is also strongly associated…”
mentioning
confidence: 99%
“…Assuming a 0.64 mmol/L (approximately 10 %) post-diet difference and a 0.8 SD [22], with α = 0.05 and 1 − β = 0.8, a minimum of twenty-five participants were required.…”
Section: Power Calculationmentioning
confidence: 99%
“…Only a few dietary clinical intervention trials have studied the effect of whole grains intake on health [20, [88][89][90][91]. For example, in a 12-week observational dietary intervention trial (n = 79), Kristensen et al examined the effect of replacing refined wheat with whole grain wheat on body weight and percent body fat [90].…”
Section: Biological Activity Of Alkylresorcinolsmentioning
confidence: 99%